2021
DOI: 10.1007/s00335-021-09867-3
|View full text |Cite
|
Sign up to set email alerts
|

A review on the role of gut microbiota in immune checkpoint blockade therapy for cancer

Abstract: Gut microbiota has been studied in relation to human health and disease prediction for decades. Also, immune checkpoints (ICPs) are enthusiastically investigated for anti-tumor immunotherapy. Recent studies show potential of gut microbiome and gut cytokines as biomarkers for carcinogenesis and response prediction of immune checkpoint inhibitor (ICI) response. Evidence has revealed that intestinal microorganisms play a major role in the effectiveness of programmed cell death 1 (PD-1) and cytotoxic T lymphocyte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…In this interesting report, fecal samples from patients responding to ICIS showed higher taxa richness compared to fecal samples of non-responders, suggesting that human microbiota could have a notable impact on responses to immunotherapy in HCC patients (90). Despite the application of gut microbiota in modulating response to immunotherapy remains far from clinical practice, the landmark role of gut microbiota in modulating innate and adaptive immunity supports makes this research avenue particularly promising (91)(92)(93)(94)(95)(96).…”
Section: Gut Microbiotamentioning
confidence: 89%
“…In this interesting report, fecal samples from patients responding to ICIS showed higher taxa richness compared to fecal samples of non-responders, suggesting that human microbiota could have a notable impact on responses to immunotherapy in HCC patients (90). Despite the application of gut microbiota in modulating response to immunotherapy remains far from clinical practice, the landmark role of gut microbiota in modulating innate and adaptive immunity supports makes this research avenue particularly promising (91)(92)(93)(94)(95)(96).…”
Section: Gut Microbiotamentioning
confidence: 89%
“…To date, few studies have examined the impact of the gut microbiome on the clinical response of ICIs, namely progression-free survival (PFS), overall survival (OS) and irAEs, although several studies have suggested a critical role for the gut microbiome in mediating responses to immunotherapies. Previous reviews have included both animal models and clinical studies and have attempted to elucidate the underlying mechanisms of dysbiosis of gut microbiota in immune responses [ 15 , 17 ]. Our current review, therefore, assesses the association between the gut microbiome and the therapeutic benefits of ICIs in metastatic advanced cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Barnesiella was reported to remove pathogenic bacterium, to eliminate the colonization of Enterococcus that are resistant to vancomycin and to restrain antibiotic-resistant bacteria from spreading [ 153 ]. It could improve anticancer compounds such as cyclophosphamide [ 154 ]. The reduction of Barnesiella was probably related to the pathogenesis of IBD.…”
Section: Food Colorantsmentioning
confidence: 99%